The Hawkins\Brown emission reduction tool. Issue 1 (2nd January 2021) - Bowles, Louisa; Attwood-Harris, Jake; Khan-Fitzgerald, Raheela; Robinson, Ben; Schwartz, Yair
Abstract : It is now globally accepted that human activity has caused rapid climate change, and the built environment is one of the biggest contributors to carbon emissions worldwide. There are primarily two ways in which the built environment generates carbon emissions: from energy used during operation (operational carbon) and from the materials used for building and maintenance (embodied carbon). While the industry is increasingly interrogating operational carbon, embodied carbon has historically been less understood. In 2012, Hawkins\Brown and the University College London Institute for Environmental Design and Engineering agreed to co-fund a doctoral project seeking to improve the visualisation of embodied carbon and its impact on the whole life carbon (WLC) of a project. One output of this research was the Hawkins Brown Emissions Reduction Tool (H\B:ERT), a BIM-based tool for rapid reporting and visualisation of embodied carbon in buildings. This paper outlines the tool's development and initial lessons learned from its use at Hawkins\Brown. H\B:ERT v1 measures embodied carbon. As it is available for free from the Hawkins\Brown website, it has contributed to the rapid rise in discussion and dissemination of information about embodied carbon and the contribution it plays in overall emissions. Version 2, which additionally measures WLC, has been fully integrated into the Hawkins\Brown design and BIM processes allowing consideration of WLC emissions from the earliest design stages alongside more traditional design drivers. The paper concludes by outlining how the tool can develop and what regulatory frameworks are required to ensure WLC decision-making becomes the standard method of approaching building and infrastructure design.